Correlation of Optic Nerve Microcirculation with Papillomacular Bundle Structure in Treatment Naive Normal Tension Glaucoma - Wataru Kobayashi; Hiroshi Kunikata; Kazuko Omodaka; Kyousuke Togashi; Morin Ryu; Masahiro Akiba; Gaku Takeuchi; Tetsuya Yuasa; Toru Nakazawa (Journal of Ophthalmology)
Purpose. To assess the association between optic nerve head (ONH) microcirculation, central papillomacular bundle (CPB) structure, and visual function in eyes with treatment naive normal tension glaucoma (NTG). Methods. This study included 40 eyes of 40 patients with NTG and 20 eyes of 20 normal patients. We used laser speckle flowgraphy (LSFG) to measure mean blur rate (MBR) in all eyes and calculated the ratio of MBR in the horizontal quadrants of tissue area ONH (temporal/nasal ratio of MBR in the tissue area: T/N MT). Clinical findings also included retinal nerve fiber layer thickness (RNFLT) and ganglion cell complex thickness (GCCT) in the CPB and macular areas, best-corrected visual acuity (BCVA), mean deviation (MD), and refractive error. Results. T/N MT was correlated with both BCVA and MD. The OCT parameters most highly correlated with T/N MT were macular RNFLT and mid-CPB RNFLT. Furthermore, T/N MT, mid-CPB RNFLT, and macular RNFLT were higher in NTG than in normal eyes. A discrimination analysis revealed that T/N MT and refractive error were independent factors indicating NTG. Conclusions. Our results suggest that T/N MT is a candidate biomarker of NTG. Furthermore, T/N MT reflects visual function, including acuity and sensitivity, and CPB structure.